Real effects of banking crises: imports of capital goods by developing countries - Michail, Nektarios A.; Savvides, Andreas (My University, 2018)
We examine the hypothesis that banking crises have real effects on developing economies by reducing imports of capital goods. We test this hypothesis by estimating a model for the determinants of imports of capital goods by a panel of developing economies during 1961 to 2010. Our results suggest that not only do banking crises have statistically significant and economically important effects on imports of capital goods, but these effects increase the longer a banking crisis lasts. Imports of capital goods are a critical component of the capital stock and the production process in developing economies and, thus, our results highlight one important channel through which banking crises may hamper the growth prospects of these economies.
Keywords: Banking; Capital; Developing world; Financial crisis